Synergy of Environmental Theology and Green Technology in Developing a Sustainable Islamic Values Based Science Curriculum - Achmad Agus Salim; Nur Fitriyanti (Khazanah: Journal of Islamic Education and Science, 2025)
The global ecological crisis and the rapid advancement of green technology have required the reconstruction of science curricula that are not only technologically oriented but also grounded in ethical and spiritual values. In the context of Islamic higher education, the integration of environmental theology and green technological innovation has not been systematically developed within curricular structures. This study aimed to analyze and formulate a conceptual framework for the synergy between environmental theology and green technology in developing a sustainable Islamic values based science curriculum. The research employed a descriptive qualitative approach using a meta-analytic method based on thematic synthesis of scientific literature published between 2016 and 2025, retrieved from the Scopus, Google Scholar, and Sinta databases. Data were collected through systematic digital documentation and analyzed using content analysis and thematic analysis. The findings indicated that the principles of tawhid, khalifah, amanah, and ecological balance functioned as epistemological foundations in framing the ethical application of green technology. A transdisciplinary curriculum model based on green technology projects was identified as the most promising approach for strengthening students’ sustainability competencies. This study contributed to the development of an integrative science curriculum model that bridges theological and technological dimensions in Islamic higher education.